Sistem Pendidikan Di Republik Rakyat China Pada Masa Pemerintahan Mao Tse Tung 1949-1959 - Khalifardhi Nursyabana; Lilis Fauziyah; Lihah Solihah; Sulaeman (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2022)
Abstract This study examines the education system of the People's Republic of China during the reign of Mao Tse Tung in the period 1949-1959. The introduction contains about Education, Mao Tse Tung's profile, and the People's Republic of China. The method used to support this research is the literature study method with an interpretation approach. The results and discussion found that the PRC government under Mao's control was centralized to the political and economic fields with the aim of making China a developed country like western countries.